Cytochrome P450s and chemoprevention. (February 2000) - Henderson, C.J.; Sahraouei, A.; Wolf, C. R.
Abstract : The cytochrome P450 mono-oxygenase system represents a major defence against chemical challenge from the environment, constituting part of an adaptive response mounted by an organism following exposure to harmful agents. Cytochrome P450s are also able to catalyse the activation of compounds to toxic products, and participate in a variety of essential 'housekeeping' functions, such as biosynthesis of steroid hormones and fatty acid oxidation. It is clear that the modulation of expression of these enzymes can have a significant effect on chemical toxicity, carcinogenicity and mutagenicity. The concept of cancer chemoprevention, i.e. the administration of a (non-toxic) chemical or dietary component in order to prevent neoplastic disease or to inhibit its progression, is an attractive one. Despite this, relatively little work has been done to characterize the ability of putative chemopreventive agents to modulate P450 expression, or to understand the interaction between P450s and chemopreventive agents. Before chemopreventive treatment can become a reality, it is essential that this complex issue is addressed; for instance, it is likely that any single chemopreventive agent will induce more than one P450 isoenzyme, and while altered expression of a particular P450 may attenuate the effects of one toxic agent, the effects of others might well be potentiated. Our laboratory has created a transgenic mouse line in which the rat CYP1A1 promoter drives expression of the β-galactosidase gene. These mice can be used to define which compounds act via the Ah receptor, in which tissues, and at which stage of development. We are currently developing another mouse line in which β-galactosidase expression is controlled by the mouse GstA1 promoter, allowing us to define the role of the antioxidant responsive element in the action of chemopreventive agents. Finally, using cre-1oxP transgenic technology, we have generated a mouse line in which P450 reductase can be deleted in a conditional, i.e. tissue-specific, manner, permitting us to investigate the role of P450s in chemoprevention in a more defined manner.